Troponin-I and left ventricular function in pediatric high-risk acute lymphoblastic leukemia after daunorubicin treatment - Rinche Annur; Didiko Hariyant; Amirah Zatil Izzah (Indonesian Pediatric Society, 2021)
Background Daunorubicin is a chemotherapy drug for leukemia treatment, but it can cause cardiotoxicity. When heart damage occurs, myocardial sarcomeres release troponin-I, which could potentially be useful as a cardiotoxicity biomarker. Objective To assess for possible correlations between troponin-I and echocardiographic parameters of left ventricular function after administration of daunorubicin in children with high-risk acute lymphoblastic leukemia (ALL). Methods This cross-sectional study on 37 children with high-risk ALL was performed from July 2017 to December 2018, in Padang, West Sumatera. The left ventricular systolic function parameters measured were ejection fraction (EF) and fractional shortening (FS); the left ventricular diastolic function parameter was E/A ratio. Troponin-I measurements and echocardiography were performed after daunorubicin treatment at the end of induction phase chemotherapy. Pearson’s correlation test was used to analyze for a correlation between troponin-I and echocardiographic parameters. Results Subjects had a mean age of 6.27 (SD 4.43) years, and males comprised 56.8%. Subjects’ mean troponin-I concentration was 5.49 (SD 0.86) ng/mL, and mean EF, FS, and E/A values were 65 (SD 5) %, 36 (SD 4) %, and 1.52 (SD 0.56), respectively. Troponin-I was not significantly correlated with EF (r=0.062; P=0.715) or FS (r=0.309; P=0.172). However, there was a weak, significant negative correlation between troponin-I and E/A ratio (r=-0.383; P=0.019). Conclusion Troponin-I level has no significant correlations with the echocardiographic parameters of left ventricular systolic function. However, there is a weak significant negative correlation between troponin-I level and the left ventricular diastolic parameter of E/A ratio.